PEMANFAATAN CLOUD GIS UNTUK PEMETAAN SUMBER DAYA ALAM INDONESIA DI PT. GEOTAMA ENERGI - Agus Sasmito Aribowo (Jurusan Teknik Informatika, 2015)
Natural resource mapping using information technology will process spatial data into more meaningful information and useful for the recipient. The conversion of natural resource data into a digital-based geographic information system being developed. Map of natural resources include spatial map of mineral deposits, oil and gas in Indonesia. The map is equipped with non-spatial data, such as the name of the location of natural resources, the amount of content, exploration history, state or corporate tenants, as well as the amount of production per unit time. This natural resource data will yield information such as maps digitally natural resources and complementary attributes. The methodology used in the development of an integrated information system are SWOT (Strong, weekness, Opportunity and Threat) Analysis and SDLC (System Development Life Cycle). The design use CASE Tools (Computer Aided Software Engineering). The system will be implemented by the architecture of cloud computing, cloud is used as a place to store the data, applications, and others to facilitate the exploration of natural resources in Indonesia. The results of the research is a prototype of GIS application for showing the locations of natural resources in Indonesia. Research can be useful for documenting the location of these resources for the parties concerned, especially the PT. Geotama Energy. Pemetaan sumber daya alam menggunakan teknologi informasi akan mempermudah pengolahan data spasial menjadi informasi yang lebih bermakna dan bermanfaat bagi penerimanya. Pengubahan data sumber daya alam menjadi berbasis digital dan berorientasi pada sistem informasi geografis terus dikembangkan. Perkembangan mengalami suatu kendala jika peta digital sulit didistribusikan kepada semua stake holder dan akhirnya akan mempersulit komunikasi data. Peta sumber daya alam meliputi peta spasial kandungan mineral, gas dan minyak bumi di Indonesia. Peta tersebut dilengkapi dengan data non spasial, misalnya nama lokasi sumber daya alam, jumlah kandungan, riwayat eksplorasi, negara atau perusahaan penggarap, serta jumlah produksi per satuan waktu. Data sumber daya alam ini akan menghasilkan informasi berupa peta sumber daya alam secara digital dan atribut pelengkapnya. Metodologi yang akan digunakan dalam pengembangan sistem informasi terpadu tersebut adalah SWOT (Strong, Weekness, Opportunity and Threat) Analysis dan SDLC (System Development Life Cycle). Dalam Perancangan digunakan CASE Tools (Computer Aided Software Engineering) berorientasi objek. Sistem akan diimplementasikan dengan arsitektur cloud computing, dimana pada sistem tersebut media internet cloud digunakan sebagai tempat menyimpan data, aplikasi, dan lainnya sehingga memudahkan dalam eksplorasi sumber daya alam Indonesia. Hasil penelitian berupa sarana berbasis GIS untuk memperlihatkan lokasi-lokasi sumber daya alam di Indonesia. Penelitian dapat bermanfaat untuk dokumentasi lokasi sumberdaya tersebut bagi pihak-pihak yang berkepentingan, terutama PT. Geotama Energy.